Facilitation of teaching and learning in selected public and private universities in Iran - Bijandi, Mohammad Sadegh (2012)
This study explored and provided the practice of facilitating teaching and learning in selected public and private universities in Iran. Qualitative approach specifically, generic inquiry was employed, because the researcher had the direct experience in this phenomenon. This study was guided by two research questions: 1) what are the conditions that facilitate teaching and learning process in higher education? 2) What are the haracteristics of facilitation in teaching and learning process among educational administrators? The data, generated through interviews as the main technique and observations and documents review as supporting techniques. Twenty nine respondents were involved in this study. Twenty of them as educational administrators were the deans of the faculties, the deputies of the deans, the lecturers and the heads of the departments. They should have at least five years experiences in teaching excluding two years experiences or still holding an administration position. And nine of them as stakeholders were students who were at least in fifth semester and alumni who graduated at most six months before.In this sense, they had plenty of information, experiences and conditions which can facilitate in the process of teaching and learning and academic achievement. The interviews were in Persian. Each interview lasted between fifty munities to one hour. The interviews were recorded, transcribed verbatim and analysed manually. Ethical issues were addressed. The trustworthiness of the study was ensured through triangulation,namely member check, peer examination and a documentation of an audit trail. Examination of the data identified that the conditions for facilitating the teaching and learning process can be classified into two groups including internal conditions and external conditions. By definition, internal conditions refer to educational administration knowledge, which is categorized into professional conditions and academic conditions. Professional conditions in terms of managerial skills are considered as team working and team building, management of personnel, budgeting and resource management, maintaining relationships, negotiation skills, and professional experiences. Data showed that by considering professional conditions by educational administrators the process of teaching and learning will be facilitated. Data also verified that the academic conditions are information literacy -up to date and access to information-, understanding the aspects of education in the area of community issues, knowing the latest mentoring and assessment methods, having the acceptable craft knowledge in teaching and learning methods and styles,understanding and supporting the societal expectations, and understanding and supporting the students needs and interests. By considering these conditions the process of teaching and learning can be facilitated External conditions refer to familiarity and knowing the aims and goals of the education and research sections in The Iran Vision Development Plan (IVDP, 2005-2025), Iran Fifth Development Plan (IFDP, 2010-2015 and Iran Higher Education National Agenda (IHENA, 2009-2013) as the National Plans. Moreover, data cleared that external conditions can facilitate the process of teaching and learning by the ability of using the facilities and financial sources that the government have considered in the IVDP, IFDP and IHENA for higher education through participating and collaborating with scientific committees and meetings. Examination of the data revealed that characteristics of educational administrators in the process of facilitating teaching and learning can be categorized into four groups including flexible, collaborative, responsive, and creative. This study has provided valuable information, which will be beneficial to all stakeholders in higher education. The study has also contributed to the notion of the process of facilitating teaching and learning higher education in Iran. Finally, it has presented a facilitation model in the process of teaching and learning in higher education.